O valor dos parceiros locais no Brasil : o efeitos dos padrões de estrutura societária e de grupos econômicos no valor das empresas em mercados emergentes - Viana, Vanessa (2010)
This study investigates how the qualitative nature of the ownership structure affects the value of publicly listed companies in Brazil within the framework of corporate governance. The work examines the interaction between firm value and five kinds of concentrated owners commonly found in emerging markets: families; public sponsors, foreign institutions, executives, and financial domestic investors. Empirical analysis shows that the mix and concentration of stock ownership do indeed significantly affect a company´s value. Using a unique data set, compiling a panel data from 2004 to 2008, the present research also develops hypotheses about the effects of business group affiliation on firm value. The investigation finds evidence that despite their importance for the development of Brazilian firms, family owners, public agents and foreign investors are giving place to more specialized, yet less concentrated monitors, such as executives and domestic financial institutions. These results indicate that corporate governance may be reaching more mature levels of development in Brazil. Further, although no relation between group membership and firm value is found, results suggest that the presence of a specific category of shareholder in one group firm facilitates future investment of the same kind of shareholder in other firms of the same group, implying that the nature of interests and conflicts among shareholders are likely to be perpetuated among the same net of colligated firms. Also, the research shows that while family partners prefer to sponsor firms with active capital mobility, foreign investors and public institutions seek out equity ventures with less capital mobility, which guarantees more transparency with respect to the uses of corporate fund.